1998
DOI: 10.1176/ps.49.11.1458
|View full text |Cite
|
Sign up to set email alerts
|

Repetitively Violent Patients in Psychiatric Units

Abstract: Even though this study focused only on serious incidents and defined recidivism narrowly, it found that recidivism of violence and aggression among psychiatric patients was a serious problem. The relative lack of response by staff members to the violent acts of recidivist patients is of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 20 publications
5
58
0
2
Order By: Relevance
“…There is considerable agreement in the literature that ward culture (Katz & Kirkland, 1990), and wards with less bstableQ patients (e.g., admission and locked wards) are most often the site of violence (Fottrell, 1980;Hodgkinson et al, 1985;Katz & Kirkland, 1990;Nijman, Allertz, à Campo, Merckelbach, & Ravelli, 1997). In several studies, it was reported that patients admitted involuntarily under mental health legislation were significantly more likely to be engaged in violent acts (Delaney, Cleary, Jordan, & Horsfall, 2001;James, Fineberg, Shah, & Priest, 1990;Owen, Tarantello, Jones, & Tennant, 1998;Powell, Caan, & Crowe, 1994;Soliman & Reza, 2001). In some studies, it was concluded that attacks often occurred when nurses were administering medication or leading or restraining agitated patients (Kalogjera, Bedi, Watson, & Meyer, 1989;Morrison et al, 2002;Soloff, 1983;Wynn, 2003).…”
Section: Determinants Of Aggressionmentioning
confidence: 99%
“…There is considerable agreement in the literature that ward culture (Katz & Kirkland, 1990), and wards with less bstableQ patients (e.g., admission and locked wards) are most often the site of violence (Fottrell, 1980;Hodgkinson et al, 1985;Katz & Kirkland, 1990;Nijman, Allertz, à Campo, Merckelbach, & Ravelli, 1997). In several studies, it was reported that patients admitted involuntarily under mental health legislation were significantly more likely to be engaged in violent acts (Delaney, Cleary, Jordan, & Horsfall, 2001;James, Fineberg, Shah, & Priest, 1990;Owen, Tarantello, Jones, & Tennant, 1998;Powell, Caan, & Crowe, 1994;Soliman & Reza, 2001). In some studies, it was concluded that attacks often occurred when nurses were administering medication or leading or restraining agitated patients (Kalogjera, Bedi, Watson, & Meyer, 1989;Morrison et al, 2002;Soloff, 1983;Wynn, 2003).…”
Section: Determinants Of Aggressionmentioning
confidence: 99%
“…Behav. DOI 10.1002/ab Delaney et al, 2001;Owen et al, 1998;Soliman and Reza, 2001]. In some studies it is concluded that attacks often occurred when nurses were administering medication or leading or restraining agitated patients [Soloff, 1983;Kalogjera et al, 1989;Wynn, 2003;Morrison et al, 2002].…”
Section: Environmental Factors and The Occurrence Of Aggressionmentioning
confidence: 99%
“…Allerdings sind diese Zahlen nur bedingt vergleichbar aufgrund unterschiedlicher Definitionen aggressiven Verhaltens, verschiedener Patientengruppen und Behandlungssettings. Übereinstimmend belegen die Studien jedoch, dass meist eine kleine Gruppe von Patienten wiederholt aggressive Handlungen begeht [15,18]. Deshalb sind selbst bei geringem Anteil aggressiver Patienten Handlungen mit aggressivem Gehalt ein nicht seltenes Ereignis auf psychiatrischen Stationen.…”
Section: Schlüsselwörterunclassified